Chemical characterization and antioxidant proprieties of Myrciaria jaboticaba bioresidues - Albuquerque, Bianca R. (2020)
Jabuticaba (Myrciaria jaboticaba (Vall.) O. Berg) is a Brazilian berry very appreciated for in natura consumption. However, its epicarp is not normally consumed, and in manufacture of products from jabuticaba fruit, it is responsible for the generation of large amounts of residues [1,2]. The exploration of by-products is becoming important for the obtainment of valuable bioactive compounds for food and pharmaceutical industries [2]. In this context, the present work aimed in the characterization of the main bioactive compounds present in jabuticaba epicarps and its potential antioxidant.